Aerobic and anaerobic energy during a 2-km race simulation in female rowers - Pripstein, L. P.; Rhodes, E. C.; McKenzie, D. C.; Coutts,K. D. (European Journal of Applied Physiology, 1999)
The average time taken for the rowers to complete the 2-km race simulation was 7.5 min, and the anaerobic system (AODpeak) accounted for 12% of the rowers' total energy production during the race.